PENGARUH PENYULUHAN KESEHATAN TENTANG MENOPAUSE TERHADAP KESIAPAN DALAM MENGHADAPI MENOPAUSE PADA IBU KLIMAKTERIUM - Khofidhotur Rofiah; Ida Tri Wahyuni; Betanuari Sabda Nirwana (Jurnal Kebidanan, 2025)
Background: Menopause is the period that a woman experiences when she is about to enter old age. Women before menopause will experience a decrease in various bodily functions. Based on the number of climacterium mothers, there are 15 mothers who are physically, psychologically or mentally not ready to enter old age or menopause. The purpose of this study is to determine the effect of health counseling about menopause on readiness to face menopause in climacterium mothers at the Tiron Health Center, Kediri Regency. Research Method: The research design used is Pre Experiment research with the One Group Pre Test Post Test Design approach. The population in this study is 34 climacterium mothers aged 40-50 years and the sample in this study is 16 climacterium mothers. The sampling technique is Purposive Sampling. Data collection was done using questionnaires and research results were analyzed using the Wilcoxon test. Research Results: Based on the results of the statistical test, p value = 0.001 (<0.05) was obtained. Conclusion: there is an effect of health counseling on menopause on menopause readiness in climacterium mothers.